HUBUNGAN ANTARA TINGKAT PENDIDIKAN MASYARAKAT DENGAN KESADARAN MASYARAKAT DALAM PEMBANGUNAN DESA (STUDI KORELASI DI DESATEMUWANGI KECAMATAN PEDAN KABUPATEN KLATEN TAHUN 2009-2010) - Widyaningsih, Nur Dewi (Prodi PPKn FKIP UNS, 2013)
The purpose of this study was to determine whether there is a positif and significant relationship between the level of public education with public awareness in rural development (the study of correlations in the Village District Temuwangi Pedan Klaten year 2009/2010).This research uses descriptive quantitative method. The population is all citizens in the years 2009-2010 Village Temuwangi aged 20-49 years, some 1468 souls. Samples were taken by cluster random sampling of some 147 souls. Variable data collection techniques and variable levels of public education awareness in rural development using a questionnaire. Technical analysis of the data used is the product moment correlation analysis to test the normality test requirements analysis, test and linearity test with a significance level of independent research by 5%.Based on the research results can be concluded that positif and significant relationship between the level of public education with public awareness in rural development (the study of correlations in the Village District Temuwangi Pedan Klaten years 2009-2010) as evidenced by rxy >rtabel or 0.1789> 0.176. Then Ho is rejected and Ha accepted.